PENGARUH JUMLAH KARGO UDARA TERHADAP KINERJA PERSONIL KARGO DI BANDAR UDARA SULTAN HASANUDDIN MAKASSAR - Oktavanda Widi Christianto; Ariyono Setiawan; Sudrajat (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Air cargo is all goods sent by air by airplane, often used by most people to send goods over long distances because of the speed factor in their delivery. The effect of a national pandemic which resulted in a decrease in the number of passengers and an increase in the number of air cargo and was not matched by the addition of personnel but there was efficiency with a reduction in personnel. This final project is based on research entitled "THE INFLUENCE OF TOTAL AIR CARGO ON THE PERFORMANCE OF CARGO PERSONNEL AT SULTAN HASANUDDIN MAKASSAR AIRPORT" to examine the problem of the effect of the amount of air cargo on the performance of cargo personnel at Sultan Hasanuddin Makassar airport. The formulation of the problem of this study is whether the amount of air cargo affects the performance of cargo personnel at Sultan Hasanuddin Makassar airport? The purpose of this study is to determine the effect of the amount of air cargo on the performance of personnel handling cargo at Sultan Hasanuddin Makassar Airport , by method used by the author in this research is descriptive and qualitative.